Youth Involvement in Pornography and Academic Engagement in Selected Secondary Schools in Kabale Municipality. - Kanyesigye, Bens Rogers (Kabale University, 2024)
The study aimed to evaluate youth involvement in pornography and its impact on academic engagement in secondary schools in Kabale Municipality, Kabale District. Specifically, it sought to identify the various forms of pornography among youth, assess the sources of pornographic materials, and establish the relationship between pornography and academic engagement. A cross-sectional research design was employed, followed by a mixed-methods approach (both qualitative and quantitative) to examine the population's characteristics and identify correlations. Quantitative data were analyzed using SPSS (Statistical Package for Social Scientists version 20.0) to obtain mean values and standard deviations, while qualitative data were analyzed narratively. Pearson's correlation coefficient (r) was used to examine the relationship between pornography and academic engagement. Key findings indicated that watching videos of naked persons on computers in the computer lab was the most prevalent form of pornography (M=4.61, SD=.490). Indecent dressing, revealing private body parts, was identified as a major source of pornographic material (M=4.61, SD=.490). The study revealed a positive correlation between pornography use and youth academic engagement, indicating a significant impact of pornography on academic engagement. Adolescents exposed to explicit materials, such as images of naked persons, sex videos, and written material, were prone to potential addiction, reduced self-control, and cognitive impairment. Social media platforms, internet sources, and private messaging applications were the primary sources of pornographic content, exacerbated by widespread internet and smartphone use, and the lack of proper supervision by parents, teachers, and school administrators. The study highlighted the complex and multi-faceted relationship between pornography and youth academic engagement, with excessive consumption of pornographic material leading to distractions, decreased focus on studies, and seeking instant gratification. This impacted youths' perceptions of relationships and gender dynamics, causing emotional and social challenges that hinder academic engagement and performance. The study concluded that addressing the relationship between pornography and youth academic engagement requires comprehensive sex education, media literacy programs, and open dialogues. These measures would empower school-going youth to make informed choices, foster healthy relationship approaches, and support their overall well-being and academic success.